HUBUNGAN JARAK KELAHIRAN DAN POLA ASUH DENGAN PENANGANAN SIBLING RIVALRY PADA USIA 3-5 TAHUN DI DESA LAMPAHAN BARAT : The Relationship Between Birth Distance And Parenting With Sibling Rivalry Handling At The Age Of 3-5 Years In West Lampahan Village - Yuliana; Idawati, Idawati; Sahara , Tuti; Rahayu, Lisnawati; Fahmi Ningsih, Aulia (LPPM - STIKES Pemkab Jombang, 2024)
In Indonesia, 75% of children experience sibling rivalry. The child’s reaction appears to be more agressive, misbehaves, hits, fusses, experiences descriptions, often unnecessary cries, and is more dependent on their mother. Based on case studies of siblings that have occurred to injure and even cause death to other siblings, the highest trigger is due to the parenting style of parents who often distinguish the treatment of their children, so it is a concern to do handling. A preliminary survey that was carried out in Desa Lampahan Barat on 30 mothers who had children aged 3-5 years with more than one child obtained 70% of the mothers revealed that their children felt sibling rivalry. The population in the research was 30 respondents who were taken as samples by using the total sampling methode. This research was Quantitative through cross-sectionsl design. The result showed that 19 respondents (63,3%) were authoritative parenting. It found that 20 respondents (66,7%) were close to birth spacing. In brief, there was a correlation between birth spacing and parenting with sibling rivalry management in aged 3-5 years children. Therefore, a researcher expected that respondents should monitor their birth spacing and create parenting properly